Managing natural resources for development in Africa a resource book - Ochola, Washington (Nairobi University of Nairobi Press, 2010)
The complex and dynamic interlinks between natural resource management (NRM) and development have long been recognized by national and international research and development organizations and have generated voluminous literature. However, much of what is available in the form of university course books, practical learning manuals and reference materials in NRM is based on experiences from outside Africa. Managing Natural Resources for Development in Africa: A Resource Book provides an understanding of the various levels at which NRM issues occur and are being addressed scientifically, economically, socially and politically. The book's nine chapters present state-of-the-art perspectives within a holistic African context. The book systematically navigates the tricky landscape of integrated NRM, with special reference to Eastern and Southern Africa, against the backdrop of prevailing local, national, regional and global social, economic and environmental challenges. The authors' wide experience, the rich references made to emerging challenges and opportunities, and the presentation of different tools, principles, approaches, case studies and processes make the book a rich and valuable one-stop resource for postgraduate students, researchers, policymakers and NRM practitioners. The book is designed to help the reader grasp in-depth NRM perspectives and presents innovative guidance for research design and problem solving, including review questions, learning activities and recommended further reading. The book was developed through a writeshop process by a multi-disciplinary team of lecturers from the University of Nairobi, Egerton University, Kenyatta University, the University of Zimbabwe, the University of Malawi, Makerere University and the University of Dar es Salam. In addition, selected NRM experts from regional and international research organizations including the World Agroforestry Center (ICRAF), the Africa Forest Forum, RUFORUM, IIRR and the International Development Research Centre (IDRC) participated in the writeshop and contributed material to the book.
Includes bibliographical references Index
Keywords: Natural resources-Africa-Management.